Surviving research on sensitive topics with young offenders - Nazirah Hassan (Scottish Journal of Residential Child Care)
Engaging young offenders in research on sensitive topics can pose many obstacles, especially for novice researchers. This article reflects on some challenges experienced in approaching children and young people in prison settings using either quantitative or qualitative approaches, mainly drawing on a recent project on bullying and victimisation in Malaysian juvenile justice institutions. The primary aim is to share practical challenges raised during the fieldwork and explain how these were handled in appropriate ways. The article discusses initial efforts, including issues in gaining access and the importance of conducting a pilot study. Included in this article are challenges related to how the researcher maintains field relations, manages the survey, and survives during the interviews.